Study Phenophysiology of The Reproductive Periode in Terms of Flowering Induction - Luh Putu Anom Sulistiawati; I Nengah Suaria; Ni Komang Alit Astiari; I Made Suarta (Warmadewa University Press, 2017)
The aim of research to determine the period of leaf repopulation, in order to form the flowering of Siam citrus plant. The study was conducted from March to December 2016, in Catur Village, Kintamani District, Bangli Regency, Bali Province. The research is descriptive so there is no special treatment given to the samples. The research is done by descriptive method, that is continuous research so that there is a thorough knowledge about the horticultural cultivation problem of tropical fruit, especially the citrus fruit, so that the physiology science of flowering and flowering is obtained in relation Get the fruit of the harvest. The citrus varieties used in this research are Siam citrus plant varieties that have been 6 years old. The number of samples observed as many as 10 plants with the observation of the period of bud shoots with observations every two days, the percentage of leaf buds, the period of shoots The period of leaf shoots, the number of shoots growing. The results showed that the cultivated Siam plants in Catur village Kintamani experienced a period of shoot growth during one period of growth 3 times in one period of growth. There are 4 stages of the period of replanting, ie 1). early shoot, 2), full shoot, 3) adult shoot and 4) dormancy shoot. The observation of the length of time required for early reproduction of approximately 12 weeks from the dormancy shoot, from early shoot to a full-time shoot period of approximately 3 weeks, furthermore for full-time shoot growth of approximately 4 weeks, to The time required adult shoots is approximately 8 weeks. For the amount of repayment during one period of growth of the Siam citrus plant for the period of replanting is the average number of developing is: 6.87 shoots/tree 2 weeks from the emergence of early buds, 15.5 shoots/tree weeks from the appearance of early buds, 26.78 shoots/trees from the emergence of early buds, 38.87 shoots/trees 8 weeks from the appearance of early shoots and 57.09 shoots/trees 12 weeks shoots/trees from the appearance of early shoots. The interest generated during the growth phase during the study was 2 times, with interest yielding an average of approximately 1985 flowers/trees. Keywords: flowering, period shoots, Siam citrus plant